1991
DOI: 10.1007/bf01645581
|View full text |Cite
|
Sign up to set email alerts
|

Linkage and independence of AIDS and kaposi disease: The interaction of human immunodeficiency virus and some coagents

Abstract: Through epidemiological considerations we conclude that full-blown AIDS may occur only if the index patient is infected by the human immunodeficiency virus (HIV) and, in addition, by some other infectious coagent. Since the dynamical behavior of the spread of AIDS cases with manifestation of Kaposi's sarcoma differs fundamentally from that of the non-Kaposi cases, we conjecture that two independent coagents (together with HIV) are responsible for the outbreak of full-blown AIDS with or without manifestation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…This view is incontrovertible" (Goudsmit, 1992). Likewise, the epidemiologists Eggers and Weyer conclude that "the spread of AIDS does not behave like the spread of a disease that is caused by a single sexually transmitted agent" (Eggers and Weyer, 1991) and hence have "simulated a cofactor [that] cannot be identified with any known infectious agent" (Weyer and Eggers, 1990). Anderson and May (1992) had to invent "assortative scenarios" for different AIDS risk groups to reconcile AIDS with infectious disease.…”
Section: Aids Not Compatible With Infectious Diseasementioning
confidence: 99%
See 3 more Smart Citations
“…This view is incontrovertible" (Goudsmit, 1992). Likewise, the epidemiologists Eggers and Weyer conclude that "the spread of AIDS does not behave like the spread of a disease that is caused by a single sexually transmitted agent" (Eggers and Weyer, 1991) and hence have "simulated a cofactor [that] cannot be identified with any known infectious agent" (Weyer and Eggers, 1990). Anderson and May (1992) had to invent "assortative scenarios" for different AIDS risk groups to reconcile AIDS with infectious disease.…”
Section: Aids Not Compatible With Infectious Diseasementioning
confidence: 99%
“…These findings argue against a sexually transmitted cause, because sexual transmission predicts a much higher AIDS risk for homosexuals with hundreds of sexual partners than for intravenous drug users (Section 4) (Weyer and Eggers, 1990;Eggers and Weyer, 1991). Indeed, numerous controlled studies have indicated that the morbidity and mor-tality of intravenous drug users is independent of HIV (Sections 4.4, 4.5 and 4.7).…”
Section: Annual Aids Risks Of Different Hiv-infected Risk Groups Incmentioning
confidence: 99%
See 2 more Smart Citations
“…This view is incontrovertible' [50]. More specifically, the epidemiologists Egger and Weyer [51] state that 'the spread of AIDS does not behave like the spread of a disease that is caused by a single sexually transmitted agent'. To reconcile AIDS with infectious dis ease they 'simulated a cofactor [that] cannot be identified with any known infectious agent' [52], The epidemiol ogists Anderson and May [53] had to invent 'assortative scenarios' for different AIDS risk groups to match AIDS with infectious disease.…”
Section: Aids Fails All Criteria Of Infectious Diseasementioning
confidence: 99%